Stability of high moisture corn silage and corn rehydrated Estabilidade de silagens de grãos úmidos de milho e milho reidratado - Silva C.M. (2016)
This work was carried out to evaluate the fermentation characteristics and aerobic stability, regarding the conventional high moisture corn grain silage (Fortuna variety), the high moisture sweet corn grain silage and the high moisture rehydrated corn silage. Data were statistically analyzed as a 3x3 factorial arrangement in a completely randomized design, and the factors were three types of corn (Fortuna, sweet and rehydrated) and three inoculation treatments (without inoculum, bacterial inoculum and bacterial inoculum plus enzymes). The aerobic stability values were assessed, collecting the temperatures from the room dry bulb and from the silage thermometers, and the pH values, at 0, 24, 48, 72, 96, 168, 192, 216, 240 and 296 hours after aerobic exposition. Additionally, different mathematical models to estimate the mean pH values after opening were tested. Interactions were observed (P<0.05) between types of corns and inoculants for aerobic stability and pH at 72, 168 and 192 hours after opening. Inoculated sweet corn silages presented better aerobic stability after aerobic exposition compared to the other silages. The sweet corn silage presented lowest pH values at 48 hours after opening. The pH values at 168 hours of rehydrated corn silage treated with bacterial inoculum plus enzymes was more acid. Richard's Equation (1959) was the best tool for the pH estimation when either types of inoculants or rehydrated corn silage were considered. On the other hand, the model proposed by Morgan et al. (1975) was the best equation model to fit the data regarding either Fortuna or sweet corn silages.